Marginal and Internal Fit of Cobalt-Chromium Fixed Dental Prostheses Generated from Digital and Conventional Impressions - Per Svanborg; Henrik Skjerven; Pablo Carlsson; Alf Eliasson; Stig Karlsson; Anders Örtorp (International Journal of Dentistry)
Objectives. Digital impressions are increasingly used and have the potential to avoid the problem of inaccurate impressions. Only a few studies to verify the accuracy of digital impressions have been performed. The purpose of this study was to compare the marginal and internal fit of 3-unit tooth supported fixed dental prostheses (FDPs) fabricated from digital and conventional impressions. Methods. Ten FDPs were produced from digital impressions using the iTero system and 10 FDPs were produced using vinyl polysiloxane (VPS) impression material. A triple-scan protocol and CAD software were used for measuring and calculating discrepancies of the FDPs at 3 standard areas: mean internal discrepancy, absolute marginal gap, and cervical area discrepancy. The Mann-Whitney U test was used for analyzing the results. Results. For conventional and digital impressions, respectively, FDPs had an absolute marginal gap of 147 μm and 142 μm, cervical area discrepancy of 69 μm and 44 μm, and mean internal discrepancy of 117 μm and 93 μm. The differences were statistically significant in the cervical and internal areas (P<0.001). Significance. The results indicated that the digital impression technique is more exact and can generate 3-unit FDPs with a significantly closer fit compared to the VPS technique.